Effect of Y2O3 on microstructure and mechanical properties of hypereutectic Al-20%Si alloy - 杨亚锋 许长林 王慧远 文0畅 姜启川 (Transactions of Nonferrous Metals Society of China, 2006)
The effect of Y203 on the microstructure and mechanical properties of the hypereutectic Al-20%Si（mass fraction） alloy was investigated. The results show that, with the addition of Y203 into the Al-P-Ti-TiC modifier, the average size of primary silicon in the Al-20%Si alloy modified by Al-P-Ti-TiC-Y203 modifier （approximately 15μm or less） is significantly reduced, and the morphology of eutectic silicon changes from coarse acicular and plate like to refined fibrous. The Brinell hardness （HB189） and tensile strength （301 MPa） of Al-20%Si alloy modified by the Al-P-Ti-TiC-Y2O3 increase by 11.6% and 10.7%, respectively, for the alloys aider heat treatment.